The Role of Arabic Language Learning in the Development and Understanding of Hadith Science - Burhanuddin, Burhanuddin; Muhammad Rezky Ramadhan; Davinna Sherenia Pramesti (al-Afkar, Journal For Islamic Studies, 2025)
Arabic plays a central role in the Islamic world as the language of the holy scriptures of the Qur'an and Hadith, the language of religion, the official language of the United Nations (UN), and the national language in over 25 countries in the Middle East. Additionally, Arabic is known as "lughah al-dhâd" with a high cultural and social heritage value. Divine protection of Arabic as the vessel of Qur'anic expression affirms its authenticity and preservation (AlHijr: 9). Mastery of the Arabic language is crucial for the development of Hadith studies, enabling direct comprehension of Hadith texts without reliance on potentially inaccurate translations. Analysis of Hadith texts and the chain of narrators (sanad) requires proficiency in grammar, vocabulary, and the cultural context of the time of Prophet Muhammad, essential for assessing the authenticity and quality of Hadith. This research employs a qualitative method with a literature review approach, analyzing materials from relevant journals and books to construct a historiographical presentation of findings. The study emphasizes that proficiency in Arabic is not only a means of communication but also a primary key to deeply understanding and interpreting the intellectual heritage of Islam.